Esthetic and functional rehabilitation of hypomineralized first permanent molars using prefabricated versus custom made zirconia crowns: a 12-month follow-up study - Rawal, Sakshi; Srivastava, Nikhil; Rana, Vivek; Kaushik, Noopur (International Journal Of Community Medicine And Public Health, 2022)
Background: Molar incisor hypomineralisation is defined as “hypomineralisation of systemic origin, presenting as demarcated, qualitative defects of the enamel of one to four first permanent molars frequently associated with affected incisors. MIH is also considered as a public health issue since it leads to pain, poor esthetics and has a negative impact on the quality of life. Thus, managing patients with MIH requires a variety of patient management approaches, materials, and techniques ranging from Intracoronal to extracoronal full or partial coverage restorations. To evaluate the efficacy of prefabricated zirconia crowns and custom-made zirconia crowns used on hypomineralised molars and to compare their efficacy in terms of gingival health, surface integrity, retention, parental satisfaction, time and cost over a time period of baseline (1day), 3, 6, 9 and 12 months. Methods: Twenty-six hypomineralized first permanent molars from children aged 7-12 years indicated for full coverage restorations were randomly selected from the Out Patient Department. The selected teeth (molars) were then randomly allocated into two groups (13 each) according to the type of crown used, namely Group A-prefabricated zirconia crowns (n=13) and group B-custom-made zirconia crowns (n=13). Tooth preparation was done according to the crown selected and all the crowns were cemented using resin-based cement. Patients were recalled and the follow-up was done by single trained examiner. Results: Clinical success for both the crowns were similar with no statistical difference between them. Conclusions: Both the crowns proved to be clinically successful.